Chrysene alters the expression pattern of HSP70 genes in mandarin fish - Yufei Liu; Tiantian Chen; Jinliang Zhao; Xiaowu Chen (Aquaculture and Fisheries)
The heat shock protein 70 (HSP70) in fish plays a crucial role in various physiological and environmental stresses. To reveal the mechanisms of the HSP70 gene response to abiotic stress in mandarin fish (Siniperca chuatsi), we analyzed the HSP70 gene family in this species. There are 16 HSP70 genes in mandarin fish, and their protein three-dimensional structures were constructed. The aliphatic index of the 16 mandarin fish HSP70sranges from 73.50 (HSPa4b) to 99.46 (HSPa13), and all are hydrophilic proteins, with seven of them being unstable proteins. After exposure to chrysene, six HSP70 genes in the intestine, four in the liver, and four in the brain tissues exhibited significant expression changes. These findings reveal that chrysene exposure affects the physiological status of fish, and HSP70 genes may play a role in the chrysene exposure tolerance of the intestine, brain and liver in mandarin fish.